2021
DOI: 10.15585/mmwr.mm7035e2
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak Associated with SARS-CoV-2 B.1.617.2 (Delta) Variant in an Elementary School — Marin County, California, May–June 2021

Abstract: MCPH) was notified by an elementary school that on May 23, an unvaccinated teacher had reported receiving a positive test result for SARS-CoV-2, the virus that causes COVID-19. The teacher reported becoming symptomatic on May 19, but continued to work for 2 days before receiving a test on May 21. On occasion during this time, the teacher read aloud unmasked to the class despite school requirements to mask while indoors. Beginning May 23, additional cases of COVID-19 were reported among other staff members, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
95
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 4 publications
8
95
0
3
Order By: Relevance
“…Overall, our findings support previous studies that have shown secondary transmission and outbreaks associated with in-person schooling and child care (22)(23)(24)(25)(26). While there are other studies that have shown relatively low risk of transmission in schools (27)(28)(29)(30)(31), SARS-CoV-2 mitigation measures were in place in each of these settings.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 89%
“…Overall, our findings support previous studies that have shown secondary transmission and outbreaks associated with in-person schooling and child care (22)(23)(24)(25)(26). While there are other studies that have shown relatively low risk of transmission in schools (27)(28)(29)(30)(31), SARS-CoV-2 mitigation measures were in place in each of these settings.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 89%
“…*** In addition, children aged 5-11 years represent a growing proportion of new COVID-19 cases reported to CDC, accounting for 10.6% of infections for the week of October 10, 2021, although children aged 5-11 years represent 8.7% of the population (4). In addition, children can contribute to transmission of SARS-CoV-2 in households and communities (5,6). A study of residual *** https://covid.cdc.gov/covid-data-tracker/#mis-national-surveillance sera from commercial laboratories in 47 U.S. jurisdictions estimated the seroprevalance in this age group to be 38% as of September 2021 (7).…”
mentioning
confidence: 99%
“…In-person education is an essential priority for the overall wellbeing, psychosocial development, and educational development of children [1,67,68], but it also increases the absolute number of contacts for children. School-based policies such as student cohorts, small class sizes, improved ventilation, routine testing, and vaccine mandates for teachers and staff can reduce in-school transmission [68,69].…”
Section: Discussionmentioning
confidence: 99%